Missing Data in the Unified Dysksinesia Rating Scale (UDysRS). Issue 5 (24th August 2018) - Luo, Sheng; Ren, Xuehan; Han, Weilu; Goetz, Christopher G.; Stebbins, Glenn T.
ABSTRACT: Objective: Identify the number of allowable missing values still permitting valid surrogate score calculation for the Unified Dyskinesia Rating Scale (UDysRS). Background: Missing data frequently occur in Parkinson's disease rating scales, and they compromise data validity, risking data exclusion from final analyses. Methods: Accessing the International Parkinson and Movement Disorder Society‐sponsored UDysRS translation databases (3313 complete scores). We sequentially removed item scores, consistently or randomly from subjective and objective sections. Lin's Concordance Correlation Coefficient compared prorated scores with complete scores. We considered prorated scores valid when Coefficients exceeded 0.95. Results: For consistently missing items, three from the subjective section and five from the objective section are allowable. For randomly missing items, seven from the subjective section and four from the objective section are permissible. Conclusions: We provide guidelines for constructing valid surrogate summary UDysRS scores with clear thresholds for retaining or rejecting scores based on missing values.